ANALISIS PELAKSANAAN KEBIJAKAN PELAYANAN KESEHATAN PADA MASA PANDEMI COVID-19 DI RSI A. YANI SURABAYA - Firda Rahayu Kusumawati; Satriya Wijaya; Novera Herdiani; Akas Yekti Pulih Asih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The high number of Covid-19 patient visits at the hospital has forced the hospital to take steps to continue to treat Covid-19 patients and provide services to general patients at the same time. Hospitals must minimize the risk of transmission and prioritize the safety of patients and health workers. The purpose of this study was to analyze the implementation of health service policies during the Covid-19 pandemic at RSI A. Yani Surabaya based on 12 World Health Organization (WHO) indicators. This research is a qualitative descriptive study with in-depth interviews to see the implementation of health service policies by identifying 12 indicators contained in WHO policies. The number of informants is 6 people. Data analysis used source triangulation and FGD techniques. The results of this study indicate that the implementation of health service policies during the Covid-19 pandemic has been carried out properly and optimally in accordance with the WHO rapid hospital readiness checklist for Covid-19 policy. The 12 indicators contained in the policy have been implemented by the Hospital as a form of effort and readiness for the Hospital to face the Covid-19 pandemic in providing health services. The conclusion of this study is that the implementation of the WHO rapid hospital readiness checklist for Covid-19 has been carried out in hospitals but has not yet been fully implemented, so input and recommendations are needed to improve its implementation.Keywords: Hospital, Policy, Health Services